Lithuania's Poles and Russians: two different perspectives - Savukynas, Virginijus (Politologija, 2000)
The need to assure the rights of national/ethnic minorities in the countries where some majority predominates is one of the primary pre-requisites of securing stable development and the achieved standards of life in every country. The author speaks for the need to forge new hypotheses and theoretical models to explain the ongoing processes. In the chapter "Sociological data" the author provides for such a hypothesis: the majority of Lithuania's Russians have chosen to follow incorporative perspective, they are bent to integrate into Lithuania's civil society. At the same time, Lithuania's Poles have chosen to follow segregation.In Lithuanian context the problemacy of national communities (minorities) has become one of the primary focuses of sociologists: there are lots of researches, financed from inside as well as from outside funds, which provide for new and ever-increasing sociological data and sociological interpretations. However, the author says, this right to research the given problem is not reserved to sociologists alone. By taking to analyze the problem of national minorities from the standpoint of cultural anthropology, the author undertakes to provide for equally fruitful and actual hypotheses. In this article he does not aim to generalize or question the validity of the conducted researches.The author refrains to analyze the perspectives and the choices of two national minorities of Lithuania: Lithuania's Poles and Russians. For that sake semiotic methods are used. The study discovered that the two studied national minorities of Lithuania share different perspectives, somewhat different self-interpretations and choices for adaptation in dominated by the other national group: for Lithuania's Poles, author claims, segregation-like perspective (attitude, disposal) is characteristic, whereas incorporation-like perspective is characteristic for the Russians of Lithuania. By proposing that the author urges to avoid speaking of the position of national minorities/groups in the given society in general terms because each of them is apt to choose a different way of behavior — different perspective — vis-a-vis the majority group. At the same time, he says that the analysis of the perspectives of the national groups cannot be assessed adequately without proper analysis of the majority identity. Only that given can different nuances be explained. Author states that the perspective (attitude, disposal) of a group is being determined not only by social, economic and demographic resources of it, but as well as by the constructed cultural identity, which can be "forged" by interactions with the majority. Therefore, according to the author, the aim of the article is to show how and to what extent does the culture, which is understood as a constellation of symbolic structures and structures of meaning, determine the structures of social reality.In the first part sociological data is presented. The author divisions along national lines in Lithuania. Boxplots and tables are given. In the second part — "Education" — the author introduces the changes that are characteristic with regard to the behavior of different ethnic groups in the sphere of education to different groups. In his opinion, changes in this realm can explain what perspective the national group, segregation or integration, chooses. Author traces dynamics of the schools where lessons are taught in native languages. For that sake graphs are presented. In the third part — "Social organizations" — the author studies the distribution of social organizations with regard to various national groups. In his opinion, social organizations is an important factor organizing the orientations of the national community. Two aspects are elucidated: whether the social organizations of the national groups are created on national or cultural basis, or some additional qualifications (social, economic) are needed to create social organization. This division is supported by stating that national groups do not limit themselves to maintaining cultural identity, they try to protect their indigenous interests in other, social, realms as well. Statistical data, that is, how many organizations do Poles, Russians have, what is their profile, etc., is given. Chapter "Statistical data" is dedicated to providing data which shows initial differences between the Russians and the Poles in social, demographic realms and education. In concluding chapter — "Two different perspectives of majority: the case of Poles and Russians" — the author postulates differences in the attitudes the majority, especially the media, shares with respect to Polish and Russian national minorities.In conclusion, the author reveals: 1. Perspectives and choices of two national minorities of Lithuania — Poles and Russians — are analyzed in this article. For that sake semiotic methods are used. The study discovered that the two studied national minorities of Lithuania share different perspectives, somewhat different self-interpretations and choices for adaptation in dominated by the other national group: for Lithuania's Poles, author claims, segregation-like perspective (attitude, disposal) is characteristic, whereas incorporation-like perspective is characteristic for the Russians of Lithuania; 2. Statistical data, which is oftentimes presented as "being capable of explaining" different perspectives, is used to verify the perspectives, that is to either negate or support it, or remain ambivalent. Three indicators classify the statistical data used: education, migration, and social standing; 3. Therefore, the necessity to analyze social relations, which are constructed by the majority with respect to minority, arises. How does the majority devise its relations with minority? What perspectives does it choose? Sociological data shows that Lithuanians are better disposed towards the Russians, not Poles. In the media an image is being formed saying that Russians are the best-integrated national minority in Lithuania, whereas Poles segregate. 4. Sociological data shows that such perspectives had already existed at the end of the IX century. In other words, with regard to Lithuanians seeking independence Poles were treated more negatively than Russians. Thus, a logic idea arises: those different perspectives of Poles and Russians were determined by different behavior of the majority, in this case — Lithuanians, with respect to them. Why does this happen? For that sake, it is necessary to analyze the stereotypes of the two national minorities. However, this is beyond the scope of the work.
Keywords: -